Pengaruh Layanan Bimbingan Kelompok Dengan Teknik Self Control Dalam Mereduksi Kecanduan Gadget - Pasaribu, Ariyani; Arsini, Yenti (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to describe the effect of group guidance services with self-control techniques in reducing gadget addiction to reduce gadget addiction in students. The method used in this research is an experimental method with a one group pre-tets (before service is provided) and post-tets (after service is provided) design. The research population was 45 students of class XI 1 and XI 2 MAS PAB 1 SAMPALI. The sample taken from the population was 12 students using purposive sampling technique. The t test analysis showed that the research results showed a decrease in gadget addiction after being given group guidance services using self-control techniques. Results of the paired sample t test, sig value. 2 tailed 0.000 > 0.005 then it can be concluded that Ho is rejected and H1, meaning that there is an influence of group guidance services with self-control techniques. It is recommended that further researchers use group guidance services with different techniques with the aim of seeing the extent of effectiveness in reducing gadget addiction in class XI MAS PAB 1 SAMPALI. This research aims to describe the effect of group guidance services with self-control techniques in reducing gadget addiction to reduce gadget addiction in students. The method used in this research is an experimental method with a one group pre-tets (before service is provided) and post-tets (after service is provided) design. The research population was 45 students of class XI 1 and XI 2 MAS PAB 1 SAMPALI. The sample taken from the population was 12 students using purposive sampling technique. The t test analysis showed that the research results showed a decrease in gadget addiction after being given group guidance services using self-control techniques. Results of the paired sample t test, sig value. 2 tailed 0.000 > 0.005 then it can be concluded that Ho is rejected and H1, meaning that there is an influence of group guidance services with self-control techniques. It is recommended that further researchers use group guidance services with different techniques with the aim of seeing the extent of effectiveness in reducing gadget addiction in class XI MAS PAB 1 SAMPALI.